Gas thermohydrodynamic lubrication and seals - Bai, Shaoxian; Wen, Shizhu, 1932- (Academic Press, an imprint of Elsevier, 2019)
Gas Thermohydrodynamic Lubrication and Seals provides contemporary theory and methods for thermo-hydrodynamic lubrication analysis in the design of gas bearings and seals. The title includes information on gas state equations and gas property, derivation of gas thermohydrodynamic lubrication equations, the theory of isothermal gas lubrication, thermal gas lubrication of rigid surfaces, gas thermoelastic hydrodynamic lubrication of face seals, vapor-condensed gas lubrication of face seals, experimental methods, and the design of gas face seals. Readers will find state-of-the-art, practical knowledge based on fifty years of research and application.